Effects of Early Balance Training on Functional Outcomes in Total Knee Replacement - Ravikumar , Ramya; Aseer, P. Antony Leo; Rubella, D. Hepzibah (Journal of Neonatal Surgery, 2025)
Falls are a major concern for Total Knee Arthroplasty patients, especially during the early postoperative period due to impaired balance, which can lead to complications and delayed recovery. Implementing evidence-based balance training may mitigate fall risks and improve patient safety preventing in adaption of impaired balance and gait. So, this study aimed to focus on balance training immediately after the total knee replacement to find out evidence- based balance training protocol which can have long lasting effects. Materials and Methods: 126 Subjects who underwent total knee arthroplasty from both genders were included in the study, into two groups. It’s a double blinded study where subjects and the analyst were unaware of group allocation. The outcomes of balance were measured using berg balance scale, functional mobility using timed up and go test and functional exercise capacity by six-minute walk test. Both the groups received active intervention for 2 weeks with 5 sessions per week. The other joint specific outcomes like pain severity using visual analogue scale and knee flexion mobility using universal goniometer were measured. These measurements were recorded at baseline, at discharge, at 2 months & 6 months of follow up. Results: Post-treatment the visual analog scale (p=0.0001), Knee mobility(p=0.0001), TUG score (p=0.0001), Berg Balance Scale (p=0.0001) and 6MWT (p=0.0001) results showed a significant difference with all outcome measures more than p=0.001 at the 6th month of follow- up. Conclusion: Significant differences were noted in the balance measures after the administration of specific balance exercise combined with standard rehabilitation exercises for TKR individuals on a long stance. Therefore, the present study recommends addition of specific balance exercise in the early post-operative phase in total knee arthroplasty patients. Overall, early balance training program proved to exhibit superior outcomes in TKA individuals with long-lasting benefits.